(untitled) (Indian Journal of Public Health Research & Development, 2020)
Burning is very dominant process to accruing material pollutants. The smoke produced from burning coconut shells of fish smoking industry is a problem that can cause health complaints of fish smoking workers, it can produce pollutants such as CO2, HC, NO2, and particulates. It is necessary to analyze the working period and time of workers’s health complaints. The purpose of this study is to analyze the working period and time of health complaints of fish smoking workers. The design is cross sectional, data collected by interviews using quisionare, analysis until bivariate stage. The results, form 65 total sample, mostly workers (60 people,92.3%) working > 5 years, mostly workers (61 people, 93.8%) working > 8 hours/day, mostly workers have a health complaints (47 people, 72.3%), there is no significant relationship between working period and health complaints (pv 0.611), there is no significant relationship between working time and health complaints (pv 0.061).